Temperature-Arousing Self-Powered Fire Warning E-Textile Based on p–n Segment Coaxial Aerogel Fibers for Active Fire Protection in Firefighting Clothing - He, Hualing; Qin, Yi; Zhu, Zhenyu; Jiang, Qing; Ouyang, Shengnan; Wan, Yuhang; Qu, Xueru; Xu, Jie; Yu, Zhicai (Nano-Micro Letters, 2023)
Firefighting protective clothing is a crucial protective equipment for firefighters to minimize skin burn and ensure safety firefighting operation and rescue mission. A recent increasing concern is to develop self-powered fire warning materials that can be incorporated into the firefighting clothing to achieve active fire protection for firefighters before the protective clothing catches fire on fireground. However, it is still a challenge to facilely design and manufacture thermoelectric (TE) textile (TET)-based fire warning electronics with dynamic surface conformability and breathability. Here, we develop an alternate coaxial wet-spinning strategy to continuously produce alternating p/n-type TE aerogel fibers involving n-type Ti3C2Tx MXene and p-type MXene/SWCNT-COOH as core materials, and tough aramid nanofiber as protective shell, which simultaneously ensure the flexibility and high-efficiency TE power generation. With such alternating p/n-type TE fibers, TET-based self-powered fire warning sensors with high mechanical stability and wearability are successfully fabricated through stitching the alternating p–n segment TE fibers into aramid fabric. The results indicate that TET-based fire warning electronics containing 50 p–n pairs produce the open-circuit voltage of 7.5 mV with a power density of 119.79 nW cm−2 at a temperature difference of 300 °C. The output voltage signal is then calculated as corresponding surface temperature of firefighting clothing based on a linear relationship between TE voltage and temperature. The fire alarm response time and flame-retardant properties are further displayed. Such self-powered fire warning electronics are true textiles that offer breathability and compatibility with body movement, demonstrating their potential application in firefighting clothing. Highlights: 1 The p–n segment thermoelectric aerogel fiber was fabricated through an alternating coaxial wet-spinning strategy. 2 Resultant alternating p–n segment thermoelectric fiber was electrically connected in series (two p–n pairs with a length of 3 cm) with an outstanding electrical conductivity of 23.76 S m−1. 3 Thermoelectric textile-based self-powered fire warning electronics exhibited sensitivity (trigger time within 1.43 s) and repeatable temperature sensing performance for firefighting clothing.